A NARRATIVE REVIEW ON DISEASES TRIGGERED BY MENOPAUSE - Emrana Rahman (Student's Journal of Health Research, 2023)
Menopause is an inherent physiological occurrence encountered by females during the midlife stage. In order to facilitate the effective management of this event among women, it is imperative to ascertain their healthcare information requirements.   It is commonly linked with the medical conditions of osteoporosis, osteoarthritis, and sarcopenia. Sarcopenia encompasses the degenerative process of age-related muscle atrophy, accompanied by a decline in muscular performance. This condition has recently gained recognition within the medical community and is understood to be exacerbated by a deficiency in oestrogen. Osteoarthritis has been found to exhibit a correlation with oestrogen deficiency in recent medical research. A locomotor disability results in a diminished quality of life. Deterioration in musculoskeletal well-being has the potential to advance to a state of frailty, leading to an elevated occurrence of falls and fractures. These subsequent events contribute to an augmented burden of ill- ness and mortality.  Healthcare providers and policymakers must prioritize their attention toward this specific cluster of disorders and incorporate preventive measures into national programs aimed at mitigating the utilization of health resources.